Semiotika Rambu-Rambu Lalu Lintas Laut - Surnata Surnata; Hayatun Nufus; Kodrat Alam; Elfita Agustini (LP4MK STKIP PGRI Lubuklinggau, 2021)
Traffic signs are part of road equipment that contains symbols, letters, numbers, as well as sentences and combinations in them and serves to provide warnings, prohibitions, orders, and instructions for road users. The color and shape of a traffic sign contain meanings that are not understood by everyone. The problem in this study is